Hubungan antara pemberian makanan pendamping air susu ibu (MP-ASI) dengan status gizi pada balita usia 6-23 bulan - Koleangan, Fionita; Malonda, Nancy Swanida Henriette; Punuh, Maureen Irinne (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Introduction: Toddlers are highly vulnerable to nutritional problems, as balanced nutritional intake determines their growth and development. One cause of nutritional problems is inappropriate food intake, particularly complementary foods, according to their age and needs, which impacts the nutritional status of toddlers. Purpose: To determine the relationship between the provision of complementary foods and nutritional status in toddlers aged 6-23 months. Method: This quantitative research used a cross-sectional approach. Conducted in Minahasa Regency, specifically within the Kakas Community Health Center, this study was conducted from April to July 2025. The sample used was 76 toddlers who met the research criteria. The instrument used was the Child Feeding Questionnaire (CFQ) to measure the criteria for complementary feeding. Results: Based on the Weight-for-Age (W/A) index, 93.4% of toddlers had normal weight and 1.3% were underweight. Based on the Height-for-Age (H/A) index, 86.8% of toddlers had normal height and 11.8% experienced stunting. Based on the Weight-for-Age (W/A) index, 81.6% of toddlers had good nutritional status and 15.8% were overweight. In this study, 81.6% of toddlers were given appropriate complementary foods, and 18.4% were given inappropriate complementary foods. Conclusion: There is a relationship between the provision of complementary foods and toddler nutritional status (weight/weight ratio) (p-value = 0.032), and there is no relationship between the provision of complementary foods and nutritional status based on the weight/age index and height/age index. Suggestion: Respondents in this study, namely mothers of toddlers, should provide complementary foods with a complete and balanced diet (rice, side dishes, vegetables, fruit, and milk) every day, in the appropriate amounts and at the appropriate times. It is also hoped that mothers will take the time to regularly take their toddlers to the Integrated Health Post so that their children can be monitored and receive nutritional education. Keywords: Complementary Foods; Nutritional Status; Toddler. Pendahuluan: Balita sangat rentan dengan masalah gizi, karena keseimbangan asupan gizi dalam tubuh menentukan pertumbuhan dan perkembangannya. Salah satu penyebab masalah gizi yaitu asupan makan yang diberikan dalam hal ini pemberian MP-ASI yang tidak sesuai dengan usia dan kebutuhannya, sehingga memengaruhi status gizi balita. Tujuan: Untuk mengetahui hubungan antara pemberian makanan pendamping air susu ibu (MP-ASI) dengan status gizi pada balita usia 6-23 bulan. Metode: Penelitian kuantitatif dengan pendekatan cross-sectional. Dilaksanakan di Kabupaten Minahasa tepatnya di wilayah kerja Puskesmas Kakas, penelitian ini dilaksanakan pada bulan April-Juli 2025. Sampel yang digunakan sebanyak 76 balita yang sesuai kriteria penelitian. Instrumen yang digunakan yaitu kuesioner Child Feeding Questionnaire (CFQ) untuk mengukur kriteria MP-ASI. Hasil: Status gizi balita berdasarkan indeks BB/U, terdapat 93.4% balita yang memiliki berat badan normal dan 1.3% balita underweight. Berdasarkan indeks PB/U, terdapat 86.8% balita dengan tinggi badan yang normal dan 11.8% balita stunting. Berdasarkan indeks BB/PB terdapat 81.6% balita dengan gizi baik dan balita dengan gizi lebih 15.8%. Pada penelitian ini, kategori pemberian MP-ASI tepat terdapat 81.6% balita dan 18.4% balita pada kategori pemberian MP-ASI tidak tepat. Simpulan: Terdapat hubungan antara pemberian MP-ASI dengan status gizi balita (indeks BB/PB) (p value = 0.032) dan tidak ada hubungan antara pemberian MP-ASI dengan status gizi berdasarkan indeks BB/U dan Indeks PB/U. Saran: Bagi responden dalam penelitian ini yaitu ibu dari balita agar dapat memberikan MP-ASI dengan menu makanan seimbang yang lengkap (nasi, lauk, sayur, buah, dan susu) setiap hari dengan jumlah dan waktu pemberian makan yang tepat. Diharapkan juga ibu dapat meluangkan waktu untuk rutin membawa balita ke posyandu agar pemantauan balita akan selalu terpantau dan tentunya ibu mendapatkan edukasi terkait gizi. Kata Kunci: Balita; Pemberian Makanan Pendamping Air Susu Ibu (MP-ASI); Status Gizi.